DINAMIKA PENGATURAN TARIF PROGRESIF BAGI PAJAK KENDARAAN BERMOTOR DI WILAYAH PROVINSI BALI - Putu Eva Ditayani Antari; Ida Bagus Agung Daparhita (VIVA THEMIS, 2018)
This study examines the impact of government policy of imposing progressive tariff for motor vehicles, as regulated in Act Number 28 Year 2009 on Regional Tax and Levy. The collection of motor vehicle tax is the authority of the provincial government, as one source of local revenue, so this type of tax is regulated both in national law and also delegated in local regulations. The local regulation governs the policy of collecting the motor vehicle tax and the amount of tax rate charged. Bali provincial government as the implementing agency began implementing progressive tariffs for motor vehicles in 2014. In the beginning of implementation phase, the progressive tariff only applied to four-wheeled vehicles, while for two-wheeled vehicles new progressive tariffs enacted in 2016. Furthermore, the rate of progressive tariff charged are also increased in percentage terms compared to the previous period. The impact of this policy implementation reviewed by gathering primary data from UPT Bapenda Bali Province located in Denpasar. The results of this study, generated by using descriptive analysis, indicated that there are various considerations for local government in making changes to the provisions of vehicle tax collection, in order to restrain the growth rate of motor vehicles while increasing local revenue.